An overview on method of cyclic shifts for the construction of experimental designs useful in business and commerce - Rashid Ahmed; M. H. Tahir; Muhammad Rajab; Muhammad Daniyal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The competitive nature of business today requires the knowledge to be able to manipulate process levels in a predictable fashion and to reduce process variation (quality control). This goal can beachieved through the use of experimentation to identify and confirm the effects of the process variables. Therefore, design of experiments should be an integral part of process management. Experimental designs such as treatment balanced, neighbor balanced and balanced repeated measurements designs, have been extensively used in different fields, especially in business and commerce. Different methods have been used for their construction but method of cyclic shifts is the easiest one. This paper provides the overview, how this method hasbeen used for the construction of the useful designs
Keywords: 330; cyclic shifts; experimental designs; competitive nature ofbusiness; polygonal designs; process management; quality control